Current developments and therapeutic potentials of exosomes from induced pluripotent stem cells-derived mesenchymal stem cells. Issue 4 (10th February 2023) - Aldoghachi, Ahmed Faris; Loh, Jit-Kai; Wang, Mong-Lien; Yang, Yi-Ping; Chien, Chian-Shiu; Teh, Hui Xin; Omar, Alfaqih Hussain; Cheong, Soon-Keng; Yeap, Swee Keong; Ho, Wan Yong; Ong, Alan Han-Kiat
Abstract : Mesenchymal stem cells (MSCs) are multipotent cells derived from adult human tissues that have the ability to proliferate in vitro and maintain their multipotency, making them attractive cell sources for regenerative medicine. However, MSCs reportedly show limited proliferative capacity with inconsistent therapeutic outcomes due to their heterogeneous nature. On the other hand, induced pluripotent stem cells (iPSC) have emerged as an alternative source for the production of various specialized cell types via their ability to differentiate from all three primary germ layers, leading to applications in regenerative medicine, disease modeling, and drug therapy. Notably, iPSCs can differentiate into MSCs in monolayer, commonly referred to as induced mesenchymal stem cells (iMSCs). These cells show superior therapeutic qualities compared with adult MSCs as the applications of the latter are restricted by passage number and autoimmune rejection when applied in tissue regeneration trials. Furthermore, increasing evidence shows that the therapeutic properties of stem cells are a consequence of the paracrine effects mediated by their secretome such as from exosomes, a type of extracellular vesicle secreted by most cell types. Several studies that investigated the potential of exosomes in regenerative medicine and therapy have revealed promising results. Therefore, this review focuses on the recent findings of exosomes secreted from iMSCs as a potential noncell-based therapy.